2019
DOI: 10.3390/electronics8010053
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Accuracy of Three Methods Based on the GIS Environment for Determining Winching Areas

Abstract: In forestry interventions such as thinning or selection cutting, appropriate road and skid trail networks are essential for efficient forest operations, but also for limiting damage to the residual stand and soil. Recently, multiple studies have shown the advantage of precision forestry and the use of a geographic information system (GIS) in forest road network planning, replacing time-consuming manual measurements and skid trail design directly in the forest. The objective of this research was to test the acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…2. The proper design of forest roads can play an important role in reducing soil disturbance [18,[55][56][57][58][59], and it is important to reduce the trail slope gradient. 3.…”
Section: Limiting and Preventing Disturbancementioning
confidence: 99%
“…2. The proper design of forest roads can play an important role in reducing soil disturbance [18,[55][56][57][58][59], and it is important to reduce the trail slope gradient. 3.…”
Section: Limiting and Preventing Disturbancementioning
confidence: 99%
“…Such problems are aggravated during poor economic conditions, as forest companies may not be able to access the quality of timber required to maintain profits [10]. In recent years, multiple studies have shown the advantage of precision forestry and the use of geographic information system (GIS) in forest road network analysis and planning [11]. This new approach allowed to further stress the forest road multifunctional aspects; in this direction, a recent paper highlighted like the combination of GIS-multiple-criteria decision-making (MCDM) [12] approaches can properly assist forest road planning for forestry and touristic purposes [13].…”
Section: Gis Applicationsmentioning
confidence: 99%
“…An example of the efficiency of GIS in forest operations planning is given in Figure 2, which is a real application by the authors of precision forest harvesting in a Central Italy turkey oak coppice forest yard, utilizing the methodology proposed by Picchio et al [11]. In the above-mentioned figure, it is possible to see the great difference in terms of skid trails number and length between a GISplanned ( Figure 2b) and a not-planned ( Figure 2a The subsequent step of GIS application in forest utilization is aimed to plan interventions considering both road network, environmental, and topographic conditions of the area.…”
Section: Gis Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Parsakhoo and Mostafa [13] have summarized the results of a road network analysis (RNA) and have evaluated the shortest path (to save travel time) in the city of Gorgan's public road network in Iran. Picchio et al [14] have tested accuracy in estimating areas accessible for winching along skid trails: they used three geographic information systems, namely the correct distance method (CDM), the real distance buffer method 12 (RDBM12), and the real distance buffer method 10 (RDBM10). However, research on forestry infrastructure supplies has not been sufficient.…”
Section: Introductionmentioning
confidence: 99%